Evaluasi Kesiapan Profesional Kesehatan dalam Mengadopsi Rekam Medis Elektronik di Fasilitas Kesehatan - Annisa Wahyuni; Dewi Oktavia (Politeknik Negeri Jember, 2024)
According to Permenkes No. 24 of 2022, health facilities must organize Electronic Medical Records no later than December 31, 2023. At the moment the health center is still in the preparatory stage. This study aims to assess the readiness of health professionals to adopt RME and the factors that influence its implementation in health centers. The research design is quantitative with a cross-sectional study approach. The data were collected using a questionnaire with a sample of 47 health professionals. Sampling uses the total-sample technique. Data analysis using chi-square statistical tests. Based on the results of the study there was no significant relationship between age, education, work experience, and profession in RME implementation (Pvalue > 0.05). However, productive age factors are best prepared to apply RME (100%). The level of education does not guarantee the readiness of officers to implement RME, nor does work experience determine the readiness of officers with a service life of 2-5 years unprepared by 95.5%. Regarding the profession, only 20% of medical and health information recorder (PMIK) officers are declared ready. It is expected that there will be socialization and training in the use of RME for healthcare professionals to be optimally organized.